1994
DOI: 10.5914/tropocean.v23i1.2679
|View full text |Cite
|
Sign up to set email alerts
|

Fitais do Recife de Coral da Ponta Verde, Maceió, Alagoas-Brasil.

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The fauna associated with different phytal assemblages was characterized by Santos & Correia (1994), who subsequently studied the Halimeda opuntia phytal of coral reefs of Ponta Verde and Pajuçara on the coast of the city of Maceió (Santos & Correia, 1995. The fauna associated with different phytal assemblages was characterized by Santos & Correia (1994), who subsequently studied the Halimeda opuntia phytal of coral reefs of Ponta Verde and Pajuçara on the coast of the city of Maceió (Santos & Correia, 1995.…”
Section: Introductionmentioning
confidence: 99%
“…The fauna associated with different phytal assemblages was characterized by Santos & Correia (1994), who subsequently studied the Halimeda opuntia phytal of coral reefs of Ponta Verde and Pajuçara on the coast of the city of Maceió (Santos & Correia, 1995. The fauna associated with different phytal assemblages was characterized by Santos & Correia (1994), who subsequently studied the Halimeda opuntia phytal of coral reefs of Ponta Verde and Pajuçara on the coast of the city of Maceió (Santos & Correia, 1995.…”
Section: Introductionmentioning
confidence: 99%
“…The macroalga such as A . fragilissima and Halimeda opuntia can aggregate with other invertebrate taxa and individuals on the Maceió coral reefs, which are exposed for a few hours during low tide (Santos & Correia , , ). The calcification and branching structure of this alga retain water during low tide, sheltering the associated organisms from the stress of emersion (Hooper & Davenport ).…”
Section: Discussionmentioning
confidence: 99%
“…On the Brazilian coast, preliminary studies on Ophiuroidea and other fauna associated with algae have included taxonomy, feeding, reproduction, and human impacts (Tommasi 1970(Tommasi , 1999Boffi 1972;Costa 2006;Figueiredo et al 2007;Paresque 2008). Qualitative and quantitative studies on the associated fauna with different phytal assemblages have demonstrated that the Ophiuroidea are an important invertebrate group on the coral reefs of the coast of Macei o in Northeastern Brazil (Santos & Correia 1994. In a study about temporal variation of the ophiuroids associated with the macroalga Halimeda opuntia (Linnaeus) J. V. Lamouroux, Santos & Correia (2001) observed two peaks of abundance of ophiuroids, one in winter and the other in summer, when the number of individuals were higher.…”
Section: Introductionmentioning
confidence: 99%
“…These reefs include a benthic fauna, which provide various natural substrates for the Polycladida, composed mainly of sponges (Cedro et al, 2007(Cedro et al, , 2011(Cedro et al, , 2013Bispo et al, 2014), corals (Correia, 2011) and bryozoans (Vieira et al, 2007(Vieira et al, , 2008(Vieira et al, , 2010. A variety of algae also provides habitats for numerous associated organisms (Santos & Correia, 1994, 1995, 2001), which are important environments for flatworms and other small invertebrates such as opisthobranch molluscs (Padula et al, 2012) and echinoderm brittle stars (Lima et al, 2011(Lima et al, , 2013. However, there is a significant lack of information, particularly about marine platyhelminthes in this region, with no record of the order Polycladida from Alagoas reef ecosystems.…”
Section: Introductionmentioning
confidence: 99%